Stabilization of antiferromagnetism in 1T-Fe_{0.05}TaS_{2} - Q. Niu; W. Zhang; Y. T. Chan; E. C. T. O'Farrell; R. Doganov; K. Y. Yip; Kwing To Lai; W. C. Yu; B. Özyilmaz; G. R. Stewart; J. S. Kim; Swee K. Goh (Physical Review Research, 2020)
1T-TaS_{2} is a prototypical charge-density-wave system with a Mott insulating ground state. Usually, a Mott insulator is accompanied by an antiferromagnetic state. However, the antiferromagnetic order had never been observed in 1T-TaS_{2}. Here, we report the stabilization of the antiferromagnetic order by the intercalation of a small amount of Fe into the van der Waals gap of 1T-TaS_{2}, i.e., forming 1T-Fe_{0.05}TaS_{2}. Upon cooling from 300 K, the electrical resistivity increases with a decreasing temperature before reaching a maximum value at around 15 K, which is close to the Néel temperature determined from our magnetic susceptibility measurement. The antiferromagnetic state can be fully suppressed when the sample thickness is reduced, indicating that the antiferromagnetic order in Fe_{0.05}TaS_{2} has a non-negligible three-dimensional character. For the bulk Fe_{0.05}TaS_{2}, a comparison of our high pressure electrical transport data with that of 1T-TaS_{2} indicates that, at ambient pressure, Fe_{0.05}TaS_{2} is in the nearly commensurate charge-density-wave phase near the border of the Mott insulating state. The temperature-pressure phase diagram thus reveals an interesting decoupling of the antiferromagnetism from the Mott insulating state.